Cost-effectiveness analysis of new remuneration project towards accountable civil service (Journal of Economic Research & Business Administration, 2021)
The article considers main aspects of transparency and accountability of government initiatives onthe example of the project of a new remuneration system for civil servants. Therefore, the author analyzesthe project’s cost effectiveness in the context of a three-year period and two pilot bodies in orderto develop recommendations for improving transformation processes. A special formula was developedand calculations were made taking into account the method of cost-effectiveness analysis based on thefactors of the conceptual model of the author’s dissertation research. Thus, in addition to the effectsindicated in the media by the authorized body (the project developer) on the factor “Human capital”,the study also covers a wider range of aspects, namely, factors such as “Leadership”, “Strategy”, “Organization”,“Resources” through the prism of “Citizen Centricity”. It was found that there were no significantpositive changes in performance during the analyzed period. And in some areas of work (such as“Organization”, “Citizen Centricity”), there is a deterioration in results. Thus, the author summarizes theactivities of local executive bodies as ineffective in relation to a two-fold increase in the wage fund. Takingthis into account and the identified “bottlenecks”, a number of recommendations for improving theactivities, including legislative initiatives, are proposed. In general, the results of the study have directpractical significance, since they build a platform for scaling the analysis to the remaining pilot bodies inorder to make timely changes during the piloting of the new remuneration system.